Public sector pensions: Rationale and international experiences - Frank Eich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
This paper is about public sector pensions, an issue that has become increasingly contentious in a number of countries in recent years, including in the United Kingdom. In the UK the public debate has focussed on the perceived generosity of these pensions, which, it is often claimed, contrasts with the pension promises made in the private sector. This paper does not attempt to answer whether public sector pension promises are relatively generous in the UK or elsewhere but instead aims to provide the bigger picture against which a discussion of public sector pension provision could be held. The origin of today's public sector pensions can be traced back at least to Ancient Rome, which offered pensions to its military personnel. Pensions to public sector workers can also be traced back several centuries even though their provision remained on an ad-hoc basis for longer, while universal pension provision for all is a creation of the modern welfare state. The issue of public sector pensions is intrinsically linked to the role of the state in society. Beyond the provision of pure public goods such as defence, the role of the state varies widely across countries, for example in the provision (and funding) of health or long-term care. The role of the state has also changed over time, for example in the telecommunications sector, reflecting technological progress and ideological changes. In most countries working for the state comes with a number of privileges (e.g. job security) but also with certain responsibilities (e.g. relinquishing the right to strike). An international comparison reveals that in a number of countries the state is also a special employer in the sense that it offers more generous pensions than the private sector. This is, however, not the case in all countries. The paper argues that the government might pursue a number of objectives going beyond poverty alleviation by offering more generous pensions but also stresses that more generally the objectives of efficiency, equity and sustainability remain desirable even in the context of public sector pensions.
Keywords: 330; Government Policy; Public sector pensions; Pension liabilities; Labour market; International comparisons